Spatial Polygamy and Contextual Exposures (SPACEs): Promoting Activity Space Approaches in Research on Place And Health. (August 2013) - Matthews, Stephen A.; Yang, Tse-Chuan
Exposure science has developed rapidly and there is an increasing call for greater precision in the measurement of individual exposures across space and time. Social science interest in an individual's environmental exposure, broadly conceived, has arguably been quite limited conceptually and methodologically. Indeed, in social science, we appear to lag behind our exposure science colleagues in our theories, data, and methods. In this article, we discuss a framework based on the concept of spatial polygamy to demonstrate the need to collect new forms of data on human spatial behavior and contextual exposures across time and space. Adopting new data and methods will be essential if one wants to better understand social inequality in terms of exposure to health risks and access to health resources. We discuss the opportunities and challenges focusing on the potential seemingly offered by focusing on human mobility and, specifically, the utilization of activity space concepts and data. A goal of the article is to spatialize social and health science concepts and research practice vis-à-vis the complexity of exposure. The article concludes with some recommendations for future research, focusing on theoretical and conceptual development promoting research on new types of places and human movement, the dynamic nature of contexts, and training.